Lactate Metabolism and Satellite Cell Fate - Nalbandian, Minas; Radak, Zsolt; Takeda, Masaki (Frontiers in Physiology, 2020)
Lactate is one of the metabolic products of glycolysis. It is widely accepted as an important energy source for many cells types and more recently has been proposed to actively participate in cell-cell communication. Satellite cells (SCs), which are adult skeletal muscle stem cells, are the main players of the skeletal muscle regeneration process. Recent studies have proposed a metabolic switch to increase glycolysis in activated SCs. Moreover, lactate, has been shown to affect SCs and myoblasts in vivo and in vitro. In this short review, we describe how metabolic variations relate with SC fate (quiescence, activation, proliferation, migration, differentiation, fusion and self-renewal), as well as discuss possible relationships between lactate as a metabolite and as a signaling molecule affecting SC fate.